Mining Rehabilitation Planning, Mining Heritage Tourism, Benefitsand Contingent Valuation - Mendes, Isabel (2013)
This article approaches the values underpinning derelict mining rehabilitation plans, their assessment in monetary terms, and reviews the empirical studies literature on this theme. The paper correspondingly contains four main aims. The first involves putting into perspective the thematic content on the rehabilitation of derelict and depressed mining areas, transforming them into mining heritage tourism products designed to trigger sustainable regional development. The second aim, concerns defining the range of benefits and values potentially arising. The third seeks to demonstrate and discuss why and how the theoretical frameworks of Total Economic Value (TEV) and economic valuation, taken together with the contingent valuation approach, enable the monetary estimation of the range of non-market individual values, through eliciting the individual’s willingness to pay (WTP) for the rehabilitation. And the fourth objective incorporates reviewing the literature on empirical studies estimating the monetary values of mining rehabilitation plans through recourse to the Contingent Valuation (CV) approach. We proceed by demonstrating that TEV, the economic valuation concept and CV are approaches appropriate to estimating the aforementioned benefits; we defend their utility as important inputs to raising the efficiency of political decision making processes and ensure local populations actively comply and participate in the rehabilitation process. Finally, we conclude that the empirical studies hitherto applied for estimating the monetary values of mining rehabilitation and remediation through recourse to CV remain very few despite the fact that this estimation type is increasingly recognised as an important tool in decision making processes on the rehabilitation of industrial cultural heritage in general, and mining heritage in particular.